Habitus, Modal, dan Arena dalam Cerbung Salindri Kenya Kebak Wewadi Karya Pakne Puri Tinjauan Bourdieu - Jatmiko, Ruruh; Abdullah, Muhammad (Sutasoma : Jurnal Sastra Jawa, 2021)
AbstractThis study aims to reveal the habitus, capital, and arena in Pakne Puri's â€œSalindri Kenya Kebak Wewadiâ€ based on the perspective of Bourdieu's literary sociology. Related to this, the formulation of the problem in this research is: how are the habitus, capital, and arena in the â€œSalindri Kenya Kebak Wewadiâ€ by Pakne Puri? This research method uses an objective approach and a discursive approach using Bourdieu's theory, namely habitus, capital, and the arena in the â€œSalindri Kenya Kebak Wewadiâ€ by Pakne Puri. The data used in this study are in the form of words, phrases, clauses, or sentences taken from one of the literary works in the form of a cursive. The source of the data for this research is the story of â€œSalindri Kenya Kebak Wewadiâ€ by Pakne Puri published by â€œPanjebar Semangatâ€ magazine edition No. 33-15 August 2009 to 50-12 December 2009. The results of this study are a description of the habitus, capital, and arena in â€œSalindri Kenya Kebak Wewadiâ€. Based on the habitus found in the Salindri character who wants to be successful in continuing his parents' batik business. These habits include the habitus of capital, the habitus of hard workers, and the habitus of never giving up. Based on the capital from Salindri, there are economic capital, cultural capital, social capital, and symbolic capital. Based on the arena, there is a business arena in which Salindri's business arena tries to carry out its functions as well as possible so that the business that is built remains afloat even at the expense of itscompetitors. Keywords: â€œSalindri Kenya Kebak Wewadiâ€, habitus, modal, arena, Pierre Bourdieu